Evaluating and communicating radiation risks for studies involving human subjects : guidance for researchers and institutional review boards : recommendations of the National Council on Radiation Protection and Measurements. (National Council on Radiation Protection and Measurements, 2020)
"The purpose of this Report is to provide guidance to researchers in preparing protocols that include ionizing radiation exposure to human subjects and to provide guidance to reviewing bodies, such as Institutional Review Boards, in the process of reviewing such protocols. This includes guidance for assessing proper utilization of radiation, estimation of risk, optimization of radiation dose, and formulation of informed consent statements with consistent, comprehensible and accurate language"-- Provided by publisher.
Keywords: Ionizing radiation -- Risk assessment.; Ionizing radiation -- Dosage.; Ionizing radiation -- Safety measures.; elektronické knihy; electronic books